Say I have three parameters:

```
m (in cell B2)
lambda (in cell B7)
mu (in cell B8)
```

where I can easily calculate

```
rho = lambda/(m*mu) (in cell B10)
```

I now want to calculate

`p0 = 1/(1 + (m * rho)^m/(m!*(1-rho)) + sum[n=1 to m-1]( (m*rho)^n / n!) ) `

How do I enter the sum?

`(1/(1+(B2 * (B7/(B2*B8)))^B2/(FACT(B2) * (1-(B7/(B2*B8)))) + ???))`

note: I’m generating these formulae in bash so I don’t need to use named cells and can re-use the generated formulae by copying the column and changing the parameters for your convenience:

```
lambda="B7"
mu="B8"
m="B2"
rho="($lambda/($m*$mu))"
echo -e "rho =\n\t$rho"
p0="(1/(1+($m * $rho)^$m/(FACT($m) * (1-$rho)) + ???))"
echo -e "p0 =\n\t$p0"
```